PENERAPAN LITERASI DIGITAL PADA UMKM BELLY JAYA TAMBELAN DI MASA PANDEMI COVID- 19 - Vanisa Meifari; Masyitah As Sahara; Aulia Dewi Gizta; Fauzi, Fauzi (Bajang Institute, 2023)
This service aims to analyze more deeply the application of digital literacy in MSMEs. This service was carried out at UMKM Belly Jaya Tambelan, Bintan Regency. By using this digital literacy application, it is hoped that it will make it easier for Belly Jaya Bintan MSMEs to understand their financial management so that these MSMEs are able to continue to survive even during this difficult pandemic. This service activity produces the result that digital literacy is very easy to apply and useful in helping Belly Jaya Bintan MSMEs in managing their finances